DECISION MAKING AUTONOMY AND HEALTH OF WOMEN IN REPRODUCTIVE AGE IN PAKISTAN - Altaf, Ghani; Zamri, Hassan; Dolly, Paul Carlo (Pakistan Journal of Social Research, 2023)
For all individuals, regardless of their age, ethnicity or other attributes, reproductive health rights are everyone’s right to make reproductive choices. Reproductive health privileges include the right to access RH related knowledge, insights and to encourage decisions along with the facilitation of reproductive health. The study focuses on the investigation of women’s sovereignty in decision making regarding their reproductive health. The data was collected through in-depth interviews and focus groups discussion to seek detailed information. A hybrid technique was used to figure out and analyze the data collected from 42 study respondents between age 15-49 years. Results reveal that husband's reported 47.61percent authority of decision making while the role of mother-in-law is reducing as the culture of nuclear family type is increasing. Women also are in a position to engage in decision making process. Patriarchal social practices, and polygyny marriages reduce the decision-making authority of women especially for their maternal health. Study is also backs up by existing studies showing that educational qualification improves the decision-making power of women. According to the Reproductive and Healthcare Rights Act 2013 by national policy of Pakistan, women have a right to reproductive health care information.